2015
DOI: 10.1016/j.pss.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Independent identification of meteor showers in EDMOND database

Abstract: Cooperation and data sharing among national networks and International Meteor Organization Video Meteor Database (IMO VMDB) resulted in European viDeo MeteOr Network Database (EDMOND). The current version of the database (EDMOND 5.0) contains 144 751 orbits collected from 2001 to 2014. In our survey we used EDMOND database in order to identify existing and new meteor showers in the database. In the first step of the survey, using Dsh criterion we found groups around each meteor within similarity threshold. M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 18 publications
(5 reference statements)
2
29
0
Order By: Relevance
“…Following the IAU rules, this shower was first reported as part of a paper in WGN, Journal of International Meteor Organization by . Independent meteor shower database searches resulted in confirmation of the existence of this shower, namely Rudawska et al (2015) and Jenniskens et al (2016) At the time of the initial finding, there were 35 meteors associated with this shower resulting in orbital parameters similar to published values for a known comet, namely 2001 W2 Batters. This Halley type comet with an orbital period of 75.9 years, has been well observed and its orbital parameters have been determined with higher precision than many other comets of this type.…”
Section: Iau Meteor Shower #549 Fan -49 Andromedids and Comet 2001 W2mentioning
confidence: 68%
“…Following the IAU rules, this shower was first reported as part of a paper in WGN, Journal of International Meteor Organization by . Independent meteor shower database searches resulted in confirmation of the existence of this shower, namely Rudawska et al (2015) and Jenniskens et al (2016) At the time of the initial finding, there were 35 meteors associated with this shower resulting in orbital parameters similar to published values for a known comet, namely 2001 W2 Batters. This Halley type comet with an orbital period of 75.9 years, has been well observed and its orbital parameters have been determined with higher precision than many other comets of this type.…”
Section: Iau Meteor Shower #549 Fan -49 Andromedids and Comet 2001 W2mentioning
confidence: 68%
“…The numbers of separated and confirmed showers in Sekanina (1976) in the database of 19 698 radio meteors he used or the 296 showers found by Rudawska et al (2015) in the collection of the ED-MOND database from the period 2001 to 2014, or the 230 meteor showers found by Jenniskens et al (2016a) searching the CAMS database of about 110 000 meteoroid orbits. Our numbers are also considerably smaller than the number of showers (707) in the considered IAU MDC list of all showers.…”
Section: Discussionmentioning
confidence: 99%
“…To separate the clusters, we have used two methods; the method of indices (MoI; Svoreň et al 2000) and the method suggested and described by Rudawska et al (2015;MoR&, hereinafter). The two methods are briefly described below.…”
Section: Procedures Of the Separation And Confirmation Of A Showermentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that anyway meteoroids are ejected with a distribution of velocities and a distribution of heliocentric distances. The identification of a parent body has recently seen a huge development thanks to multi-years surveys (Jenniskens et al, 2011;Rudawska et al, 2015;Colas et al, 2014). The accumulation of tens of thousands of meteoroid orbits allows one to better recognize otherwise undetected showers, and dynamical links are based on orbital similarity.…”
Section: Strategymentioning
confidence: 99%